HUBUNGAN TINGKAT PENGETAHUAN ANEMIA, PERILAKU KEPATUHAN MENGKONSUMSI TABLET FE DAN STATUS GIZI (LILA) DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS KELURAHAN SLIPI 1 TAHUN 2020 - Gelory Putri Alona Br Tarigan (2021)
The period of pregnancy is a condition where the women's body requires maximum nutritional intake. During pregnancy, mothers often complain because they feel tired easily, have respiratory problems, pale faces, and other complaints. This complaint is a symptom that the mother is experiencing anemia during pregnancy. This study aims to determine the relationship between the level of knowledge of anemia, behavior in consuming Fe tablets, and nutritional status (MUAC) with the incidence of anemia in pregnant women at Puskesmas Kelurahan Slipi I in 2020. This research uses cross-sectional design with purposive sampling technique. The selected sample was 65 pregnant's women who had gestational age in the second and third trimesters. Data were collected and collected using a questionnaire and measuring instruments such as LiLA tape. The data obtained were tested using the Chi-Square test. The results of the analysis showed that the knowledge level of anemia (p = 0.000), behavior in consuming Fe tablets (p = 0.000), and nutritional status (MUAC) (p = 0.017). There is a relationship between knowledge level of anemia, behavior consuming Fe tablets and nutritional status (MUAC) with anemia events in pregnant women at the Puskesmas Kelurahan Slipi 1 in 2020.